PERSEPSI MASYARAKAT SEKUPANG TERHADAP KEPEMIMPINAN MUHAMMAD RUDI SEBAGAI WALIKOTA BATAM - Raissa Sofia Martin; Bismar Arianto; Sayed Fauzan Riyadi (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This study examines the leadership of Mayor Muhammad Rudi as the first leader to concurrently serve as Mayor of Batam and head of BP Batam. This study aims to describe the perception of the people of Sekupang District towards Muhammad Rudi's leadership as Mayor of Batam. The theory used in this study is the leadership theory of Path-Goal. The theory of Path-Goal has 4 indicators, namely steering leadership, supporting leadership, participatory leadership, and achievement-oriented leadership. The method used in this study is quantitative method. The research location is in the Batam area of Sekupang District by taking 7 villages, from Tiban Baru, Tiban Lama, Sungai Harapan, Tanjung Riau, Tanjung Pinggir, Patam Lestari, and Tiban Indah Villages. Data was collected using questionnaires distributed to 100 respondents spread across 7 sub-districts. The data is analyzed using a percentage formula. Based on the results of research from the four indicators of directed leadership get a percentage value of 77.86% with the good category, supporting leadership gets a percentage value of 77.6% with the good category, participatory leadership gets a percentage value of 72.2% with the good category, and achievement-oriented leadership gets a percentage value of 78% with the good category. The conclusion of the four indicators consisting of 12 statements using the percentage formula that public perception produced for the assessment of the overall leadership indicators of Muhammad Rudi as Mayor of Batam is 95.52% is at the Likert scale interval of 81-100% with the very good category.   Keywords : Perception, Leadership, Mayor